PENGELOLAAN REKAYASA LALU LINTAS DAN PEMBARUAN FASILITAS PEJALAN KAKI DI RUAS JALAN BABAT, LAMONGAN - Afrizal Ghozi Habibi; Nugroho Utomo; Fithri Estikhamah (Racic : Rab Construction Research, 2026)
The increasing intensity of economic activity and traffic movement in the Babat Highway area, Lamongan Regency, has given rise to various transportation problems, particularly related to the performance of pedestrian facilities and road capacity. This study aims to analyze the level of service (LOS) on existing pedestrian paths and road sections and to develop effective traffic engineering management strategies to accommodate community mobility needs. The methodology used includes a primary survey in the form of traffic counting and spot speed studies for pedestrians and motorized vehicles. The data obtained were then analyzed using the 2014 Indonesian Road Capacity Guidelines (PKJI). The results show that the pedestrian path has not met minimum service standards, characterized by low LOS values ​​and high conflicts between pedestrians and vehicles. In addition, the road section shows a degree of saturation (DS) value that is close to the capacity threshold, indicating the need for traffic engineering interventions. The resulting recommendations include redesigning sidewalks by taking into account user dimensions and needs, rearranging parking spaces, controlling side obstacles, and improving road geometry. The implementation of this strategy is expected to improve safety, movement efficiency, and comfort for road users in a sustainable manner.